1979
DOI: 10.2136/sssaj1979.03615995004300050032x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Tagged Fertilizer Nitrogen Applied to Winter Wheat

Abstract: A field experiment using ammonium sulfate tagged with 7.65 A% 15N was conducted to assess how rates and times fertilizer is applied influence the fate of N applied to winter wheat (Triticum aestivum L.). Bottomless metal boxes were pressed 142 cm into the soil to confine the tagged fertilizer. Treatments, replicated four times, consisted of two rates (50 and 100 kg N/ha) and two application times (fall and spring). Fertilizer N used by the crop and that remaining in the upper 180‐cm of the soil after harvest w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0
4

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 0 publications
3
17
0
4
Order By: Relevance
“…The rather small fraction of residual fertilizer found in the soil may be compared with values obtained by other investigators which were either slightly more elevated (Van Cleemput and Baert, 1984;Olson et al, 1979;Strebel et a1.,1980) or markedly higher (Van Cleemput et al, 1981;Leitch and Vaidyanathan, 1983;Olson, 1982;Olson and Swallow, 1984) than our own results.…”
Section: Unaccounted Fertilizer N Residual Fertilizer In Soilsupporting
confidence: 70%
See 1 more Smart Citation
“…The rather small fraction of residual fertilizer found in the soil may be compared with values obtained by other investigators which were either slightly more elevated (Van Cleemput and Baert, 1984;Olson et al, 1979;Strebel et a1.,1980) or markedly higher (Van Cleemput et al, 1981;Leitch and Vaidyanathan, 1983;Olson, 1982;Olson and Swallow, 1984) than our own results.…”
Section: Unaccounted Fertilizer N Residual Fertilizer In Soilsupporting
confidence: 70%
“…The application of fertilizer N did not lead to any increase in soil N uptake by the crop, ruling out the possibility of added nitrogen interaction (ANI) (Jenkinson et al, 1985). Moreover, recent field experiments have shown that the amount of soil-derived N taken up by the wheat crop is not influenced by the time of split application, by the splitting pattern and by the amount of the applied fertilizer (Leitch and Vaidyanathan, 1983;Olson et al, 1979;RecousPeuch Lestrade, 1983;Remy, 1985). Table 5 shows the percent nitrogen derived from the fertilizer (%NDFF) for each split application calculated for the different plants parts, namely, the grain, straw, and crown, the latter including I cm stubble and the larger roots as indicated above.…”
Section: Soil-and Fertilizer-derived Nmentioning
confidence: 98%
“…Harris et al ( 1994) found more applied fertilizer N loss during a drought year than during a normal one. Olson et al (1979) found 100 kg N ha 1 rate plots had twice as much fertilizer N that was unaccounted for as did the 50 kg N ha' 1 rate plots. They also found most of the fertilizer remaining in the soil was in the top 0-10 cm layer of soil, with no sign of N below 50 cm.…”
mentioning
confidence: 84%
“…Webster et al (1986) found 22% of the fertilizer applied in the first year remained in the soil at the end of the growing season; slightly more than half of which was found in the upper 15 cm. Olson et al ( 1979) found 70-75% of the total fertilizer N was in the top 10 cm of the soil profile, while 70-91% was in the top 20 cm. Reddy and Reddy(1993)foundthatthe first 15 cm of the soil profile contained one-half of the residual N. Harris et al (1994) noted that the microbial biomass recovered up to 6% of the applied fertilizer N, while the nonbiomass organic fraction contained 14% of the applied N.…”
mentioning
confidence: 97%
See 1 more Smart Citation